Update Terapi Demensia Alzheimer: Antara Bukti Klinis dan Kontroversi - Pasaribu, Anastasia Ezragitha Soligaon; Umbul, Melya Arianti (Majalah Kedokteran Indonesia, 2025)
Alzheimer's dementia is a progressive neurodegenerative disease characterized by the accumulation of β-amyloid and tau, leading to cognitive decline. 1 The incidence of Alzheimer's dementia worldwide is increasing rapidly and is currently estimated to approach 46.8 million or 50 million people diagnosed with dementia worldwide, with 20.9 million in the Asia Pacific region, with approximately 10 million new cases occurring annually. 1 In Indonesia, an estimated 1.2 million people were diagnosed with dementia in 2016, with this number expected to increase to 2 million in 2030 and 4 million in 2050.1